Extensão popular e formação em Pedagogia: estudo com base em experiências na Universidade Estadual da Paraíba - Mélo, Celâny Teixeira de (2021)
This study, linked to the research line of Popular Education of the Post Graduation Program in Education of the Paraíba Federal University, approaches the Popular Extension of the Pedagogy course in the present time, having as empirical field the Paraíba State University, campus I in Campina Grande, Paraíba. It is considered that the university is a locus for professional and human shaping and that its Extension activity promotes a relationship between the university and the society contributing to assume its social commitment and promote the formation of its students, immersed in the reality for the knowledge output, possibly useful to solve social problems and to achieve transformation. This way, the main purpose of this dissertation was to analyze the Popular Extension in the Pedagogy course in the present time through the Paraíba State University. The study takes way from the perspective of the Dialectical Historical Materialism. The participants were five students from the Pegadogy course in Paraíva State University, campus I, who acted in an Extension Project in Pedagogy from 2018 to 2019. The research, which used a qualitative approach, was organized to be fulfilled in three steps. The first step constitutes in a bibliographical research ni the CAPES scientifical production database; SciELO and in the CAPES periodicals website, looking for works about the perspective of the Popular Extension developed in the Pedagogy course. The second step was constituted by a Documental Research through the access of Extension Programs from 2019 to 2019 developed in the Extension Program in the Pedagogy course of Paraíba State University, intending to locate the Popular Extension in them. The third step was constituted by a Semi- Structured interview composed of six questions (made through WhatsApp and transcripted), searching for comprehension and looking for the potentialities, difficulties, and challenges of the Popular Extension in the Pedagogy Course of the Paraíba State University. The results obtained from the Bibliographical Research were analyzed through the Dialectics in Freire; the ones from the Documental Research and the Semi-Structured Interview were analyzed by the Meaning Core. Since the first step, it was possible to notice the lack of publications focused on the Popular Extension in the Pedagogy course; the second step indicates that in the Pedagogy course of the Paraíba State University exists an initiative in some Extension Programs passed by the principles of Popular Education; the third step reveals that the Popular Extension. From the first step, it was possible to notice the lack o publications focused on Popular Extension on the Pegadogy course; the second step indicates that the Pedagogy course of the Paraíba State University have initiatives in some Extension Projects passed through the principles of Popular Education; the third step reveals that the Popular Extension impacts in the formation in Pedagogy, through the promotion of a dialogue between the university and the community in a horizontal shape, permeated by theory and practice in the ways of the práxis, for a problematizing and liberating education, through the interaction of subjects in the construction of knowledge, approximation of reality of the other and the world, culminating in an emancipatory education. In the opposite way of these potentialities of the Extension, its found the lack of funding and Studies about Popular Extension and other Extension Projects with perspective on the Popular Extension in the course. What points to the challenges of introducing in the Pedagogy Course the possibilities for the students to have access to study Popular Extension. It's believed that this study showed the relevance and meaning of the Extension guided by principles of Popular Education in the formation of professionals in Pedagogy by the potentialities of the insertion in educational spaces marked by a relation of dialogue between the university and the society. As also instigates the challenge of ways on the construction of knowledge about the Popular Extension and its realization on the Pedagogy Course of the Parapiba State University and other Brazilian Universities.